Role of the user in the development of the lexicon - Atarji, Sami bin Mohammed Ghaleb (Journal of Humanities & Social Sciences, 2017)
Dictionaries epitomize prominent semblance of the written literature that originated and flourished to form a record of the language of its time. The early pioneering authors of Arabic dictionaries were unprecedented in compiling entire dictionaries that absorbed a living language heritage of science and arts. One of the most remarkable of those pioneers and the first historically is Al-Khalil Ibn Ahmed Al-Faraaheedi who has devised through his linguistic insightfulness a phonetic illustration for the arrangement of content. Among the fundamentals of structuring a dictionary is the manifestation it reveals to the readers, or as they are technically identified as ‘users’. Lexicography has matured in the developed countries to be a renowned discipline of many facets, with scientific principles that deal with the details of the industry. Lexical studies have occupied also a significant quantity of modern linguistic studies. The role of the user of the dictionary has become one of the most key lexicographic guidelines before and after the compilation of the dictionary in addition to the settings of commercial objectives that are determined by the publishing houses according to economic studies. As a result, it was inevitable for the Arabic language counterparts to pursue the expeditious scientific and technological developments, and to increase investment in the field of authoring and publishing all types of dictionaries in accordance with modern demands.